PELESTARIAN BUDAYA LOKAL MELALUI PEKAN GAWAI DAYAK DI KABUPATEN SINTANG - Sim, Emiliani Nindy Diana (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2024)
The development of the global world has indirectly shifted the meaning of local culture withinsocieties. With the introduction of a more modern system of work and thinking, the traditional life systemof society has changed. Even though people's lifestyles are becoming more modern, it doesn't mean that thetraditional local culture is not preserved and just abandoned. This study was conducted with the aim ofunderstanding the preservation of local culture through Pekan Gawai Dayak in Sintang District. Theresearch approach used in this study is qualitative descriptive method with literacy study. Through literacystudies, researchers gather relevant information from various sources, such as journals, news portals andsocial media. The results of the study found that, the Government of the District of Sintang along with theAdelantary Council of Dayak district Sintang carried out a cultural celebration of Pekan Gawai Dayak asone of the efforts to preserve the local culture. In its implementation, Pekan Gawai Dayak presented variouslocal cultural activities of the Dayak community in Sintang district. The effort to preserve the local cultureis not an impossible thing to do, because the enthusiasm of the community is always high every PekanGawai Dayak carried out. Therefore, it is necessary to innovate and refine the location of the activities inorder to encourage the participation of the public as participants and beneficiaries of the culturalcelebrations by the Sintang District Government